UPF1 internal ribosome entry site-mediated translation and its importance in tumorigenesis - Lacerda, Rafaela (2021)
Aims: UPF1 internal ribosome entry site-mediated translation and its importance in tumorigenesis; Confirm UPF1 5’ untranslated region (UTR) can mediate internal ribosome entry site (IRES)-mediated translation; Check whether the IRES-dependent translation is maintained under cap-dependent-impairing conditions (hypoxia); Identify the minimal sequence required for IRES-mediated translation; Investigate the biological role of UPF1 IRES-mediated translation in tumorigenesis.